Creating Positive Systems of Child and Family Welfare : Congruence with the Everyday Lives of Children and Parents - Cameron, Gary (Book collections on Project MUSE., 2013)
"The North American approach to child protection is broadly accepted, despite frequent criticisms of its core limitations: parental fear and resistance, the limited range of services and supports available to families, escalating costs, and high stress and turnover among service providers. Could these shortcomings be improved through organizational or system reform? Based on findings from a decade's worth of research, Creating Positive Systems of Child and Family Welfare provides original reflections on the everyday realities of families and front-line service providers involved with the system. It includes data from a variety of regions and situations, all linked together through a common investigatory framework. The contributors highlight areas of concern in current approaches to child and family welfare, but also propose new solutions that would make the system more welcoming and helpful both for families and for service providers."--Publisher's website